APLIKASI PEMBERIAN KOMPOS TITONIA DAN PUPUK GRAND-K TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) PADA TANAH GAMBUT - Asih Pengestuti; Fathurrahman; Siti Zahra (Ekoagrotrop, 2023)
Application of titonia compost and Grand-K fertilizer on growth and production of shallots (Allium ascalonicum L.) on peat soil has been conducted at the Faculty of Agriculture, Universitas Islam Riau starting from June to August 2021. This is research aimed to know the effect of interaction and each of the main factors of Titonia compost and Grand-K fertilizer on the growth and yield of shallots in peat. The design used in this study is completely randomized design (CRD) factorial consisting of two factors. The first factor is the doses of Titonia Compost which consists of 4 levels, namely 0, 15, 30, and 45 g per polybag. The second factor is the doses of Grand-K fertilizer which consists of 4 levels, namely 0; 0.40; 0.80 and 1.20 g per polybag. Parameters observed were relative growth rate, plant height, number of tubers per clump, wet tuber weight per clump, tuber diameter, dry tuber weight per clump, dry weight of biomass, measurement of pH and plant nutrient uptake. The observational data were analyzed statistically and continued with further real difference honest test at the 0,05 level. The results showed that the interaction of titonia compost and Grand-K fertilizer was significant on the parameters of the number of tubers per clump, wet weight of tubers per clump, dry weight of tubers per clump and dry weight of biomass. Combination The best treatment was the dose of titonia compost 45 g/polybag and Grand-K fertilizer 0.80 g/polybag. The main effect of titonia compost was significant on all observed parameters. The best treatment was the dose of titonia compost 45 g/polybag. The main effect of Grand-K fertilizer dose was significant on all observation parameters. The best treatment was a dose of 0.80 g/polybag Grand-K fertilizer.